Pharmacokinetic Interactions Between Isavuconazole and the Drug Transporter Substrates Atorvastatin, Digoxin, Metformin, and Methotrexate in Healthy Subjects. Issue 1 (15th July 2016) - Yamazaki, Takao; Desai, Amit; Goldwater, Ronald; Han, David; Lasseter, Kenneth C.; Howieson, Corrie; Akhtar, Shahzad; Kowalski, Donna; Lademacher, Christopher; Rammelsberg, Diane; Townsend, Robert
Abstract: This article summarizes 4 phase 1 trials that explored interactions between the novel, triazole antifungal isavuconazole and substrates of the drug transporters breast cancer resistance protein (BCRP), multidrug and toxin extrusion protein‐1 (MATE1), organic anion transporters 1/3 (OAT1/OAT3), organic anion‐transporting polypeptide 1B1 (OATP1B1), organic cation transporters 1/2 (OCT1/OCT2), and P‐glycoprotein (P‐gp). Healthy subjects received single doses of atorvastatin (20 mg; OATP1B1 and P‐gp substrate), digoxin (0.5 mg; P‐gp substrate), metformin (850 mg; OCT1, OCT2, and MATE1 substrate), or methotrexate (7.5 mg; BCRP, OAT1, and OAT3 substrate) in the presence and absence of clinical doses of isavuconazole (200 mg 3 times a day for 2 days; 200 mg once daily thereafter). Coadministration with isavuconazole increased mean area under the plasma concentration‐time curves (90% confidence interval) of atorvastatin, digoxin, and metformin to 137% (129, 145), 125% (117, 134), and 152% (138, 168) and increased mean maximum plasma concentrations to 103% (88, 121), 133% (119, 149), and 123% (109, 140), respectively. Methotrexate parameters were unaffected by isavuconazole. There were no serious adverse events. These findings indicate that isavuconazole is a weak inhibitor of P‐gp, as well as OCT1, OCT2, MATE1, or a combination thereof but not of BCRP, OATP1B1, OAT1, or OAT3.